2016
DOI: 10.1089/neu.2015.4327
|View full text |Cite
|
Sign up to set email alerts
|

Primary Blast Exposure Increases Hippocampal Vulnerability to Subsequent Exposure: Reducing Long-Term Potentiation

Abstract: Up to 80% of injuries sustained by U.S. soldiers in Operation Enduring Freedom and Operation Iraqi Freedom were the result of blast exposure from improvised explosive devices. Some soldiers experience multiple blasts while on duty, and it has been suggested that symptoms of repetitive blast are similar to those that follow multiple non-blast concussions, such as sport-related concussion. Despite the interest in the effects of repetitive blast exposure, it remains unknown whether an initial blast renders the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Our observation that primary blast exposure causes broad changes in glial reactivity with no significant evidence of neuronal loss or degeneration is consistent with some past rodent (Svetlov et al, 2010) and porcine models of bTBI (Bauman et al, 2009; de Lanerolle et al, 2011), and some aspects of past in vitro work (Effgen et al, 2014; Effgen et al, 2015; Vogel et al, 2015). Similar to our data on hippocampal circuit alterations, we did not observe a significant dose response in glial reactivity between the lower- and higher-level blast overpressure loading.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our observation that primary blast exposure causes broad changes in glial reactivity with no significant evidence of neuronal loss or degeneration is consistent with some past rodent (Svetlov et al, 2010) and porcine models of bTBI (Bauman et al, 2009; de Lanerolle et al, 2011), and some aspects of past in vitro work (Effgen et al, 2014; Effgen et al, 2015; Vogel et al, 2015). Similar to our data on hippocampal circuit alterations, we did not observe a significant dose response in glial reactivity between the lower- and higher-level blast overpressure loading.…”
Section: Discussionsupporting
confidence: 88%
“…Preclinical rodent studies show blast exposure will cause alterations in hippocampal microstructure, increases in different forms of phosphorylated Tau, reductions in axonal conduction velocity, and LTP deficits in the hippocampal circuitry after injury (Budde et al, 2013; Effgen et al, 2015; Goldstein et al, 2012; Huber et al, 2013; Vogel et al, 2015; Yin et al, 2014). We demonstrate that despite no clear sign of neuronal loss, blast exposure will reduce hippocampal network excitability in area CA1, and that these changes do not differ across these two blast exposure levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term potentiation is the primary experimental model for investigating synaptic plasticity on a cellular level and is known to occur within the hippocampus (Bliss and Collingridge, 1993). It is well-documented that blast exposure in animals negatively affected hippocampal LTP, but this observation was not universal among preclinical models of blast TBI (Effgen et al, 2016; Goldstein et al, 2012; Huber et al, 2013; Vogel et al, 2016a; Yin et al, 2014). We have previously reported that 24 h post-injury, primary blast reduced the expression and phosphorylation of AMPA-GluR1 subunits (Vogel et al, 2016b), a key transmembrane receptor required for the induction and maintenance of LTP (Lee et al, 2000; Makino and Malinow, 2009; Mammen et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…In comparison, our in vitro primary blast injury model isolates the shock wave component of blast from the other, confounding phases of injury (Effgen et al, 2012). The precisely controlled biomechanics of our injury model enables the study of neuronal dysfunction following primary blast injury in isolation (Effgen et al, 2012, 2016; Hue et al, 2014; Vogel et al, 2016b). …”
Section: Introductionmentioning
confidence: 99%